Biofeedback and shooting performance: A test of disregulation and systems theory - Daniels, F.S.; Landers, D. M. (Journal of Sport Psychology, 1981)
This study investigated heart rate (HR) and respiration functioning during rifle shooting to test hypotheses derived from G. E. Schwartz's (1979) systems and disregulation theory and to compare biofeedback with verbal instruction in developing awareness and control of autonomic patterns. According to Schwartz's model, as long as the S processes stimuli that connect the negative biofeedback loop, autonomic self-regulatory changes between brain, body, and the biofeedback will occur. Eight male Ss aged 18-20 yrs were pretested to determine HR and respiration patterns affecting performance. They were then divided into 2 groups and given either auditory-biofeedback via continuous pattern feedback through earphones or presession verbal introduction without feedback. Each group trained and was then tested over 2 40-shot sessions. A scaled interview was administered pre- and posttraining to determine awareness/control of autonomic functioning. Compared to verbal instruction group, the biofeedback group significantly improved performance and consistency of the desired pattern and had significantly greater awareness/control of the autonomic pattern. The results support the systems and disregulation theory as well as the viability of biofeedback for altering imbalances within the systems. (10 ref) (PsycInfo Database Record (c) 2022 APA, all rights reserved)